Correlation and prevalence of recurrent aphthous stomatitis with stress among undergraduates in private dental institutions of Lahore, Pakistan - Malik Adeel Anwar; Ijaz Ur Rehman; Tahmasub Faraz Tayyab; Maidah Shoaib; Sofia Awais; Moghees A Baig (Journal of University Medical & Dental College, 2025)
ABSTRACTBACKGROUND AND OBJECTIVE: Oral ulcers, commonly associated with stress, serve as significant indicators of psychosomatic interactions impacting oral health. Stress is known to compromise the immune system, making individuals susceptible to various health challenges. This study aimed to explore the intricate connection between recurrent oral ulcers and stress among dental students in Lahore, Pakistan.METHODOLOGY: This descriptive cross-sectional study was conducted in multiple private dental colleges in Lahore. Non-probability consecutive sampling was employed, and the calculated sample size was 598. Data collection utilized a pre-validated questionnaire with two sets of closed-ended questions rated on a 5-point Likert scale. Statistical analysis was performed using SPSS version 25, and the Chi-square and Fisher exact tests were applied to assess the association between ulcers and stress.RESULTS: Out of 598 participants, 51.3% reported a history of oral ulcers, with 7.82% of participants reporting current oral ulcers. Notably, 47.23% had oral ulcers within the past six months, and the majority (66.45%) experienced 2-6 ulcers per episode. The duration of ulcers predominantly ranged from 1-2 days (38.20%). Family history was significant (51.47%), and stress was identified as a major cause, especially during examinations (68.4%). Perceived stress scores were high among the previous history of oral ulcers group (p=0.001).CONCLUSION: This research reveals a compelling association between stress and recurrent oral ulcers, underscoring stress as a crucial factor. The results of this study will help to improve the quality of life of dental students, either by addressing their stress levels or by recommending appropriate remedies.